Bringing children back into the family : relationality, connectedness and home - Frankel, Sam; McNamee, Sally (Sociological studies of children and youth, 2020)
Theorists in the UK have offered a new perspective through which to understand the interrelationship of the individual within the structure of the family. This volume's desire is to re-apply such thinking in the context of children's lives in the family.